Analisis Perbandingan Kehilangan Prategang Akibat Variasi Letak Tendon PC I Girder Jembatan Beton Prategang - Ibham Yamin; Siswanti Zuraida; Ilham Ilham (Institut Teknologi Sains Bandung, 2020)
Prestressed force loss always occurs in prestressed concrete (loss prestressed). The most common form used in pre-tensile beams is straight tendons and for post-tensile beams are curved tendons. In planning a prestressed concrete bridge structure, the loss of prestressed force must be considered, because the stress on the prestressed concrete tendon decreases continuously over time. The number of factors that are interrelated, for the effectiveness of the design, location of tendons along the spans need to be considered, so that the tensile strength that occurs in the extreme fiber beam is limited or none at all in the cross section. This final project will examine the shape of the PC beam I Girder with 4 tendon setting conditions namely straight tendon cable which is on the neutral axis so that the eccentricity = 0 (condition1), straight tendon cable which is at 1/6 h so that the eccentricity ≠ 0 (condition 2), tendon cable with draped / parabolic shape (condition 3), and tendon condition with harped shape (condition 4). The biggest prestressed loss results were PC I Girder (condition 2) = 395.81 MPa (26.07%), while the smallest prestressed loss is PC I Girder (condition3) = 367.44 MPa (24.2%). Condition 1 and 2 in girder is not suitable for use because it exceeds the value of the allowable stress at the limit of prestressed and deflection permits on girder are safe for each condition.